Investigasi Pendugaan Gerakan Tanah Menggunakan Metode Electrical Resistivity Tomography dan Self Potential di Daerah Pasanggrahan Baru, Sumedang Selatan - Budy Santoso; Subagio Subagio; Mia Uswatun Hasanah; Hilman Suwarga (Pusat Survei Geologi, 2020)
Land movement occur because of the movement of slope-forming material such as of soil, rock or a combination of material types to a place that is lower due to the influence of gravity. The movement of slope material can be identified by the Electrical Resistivity Tomography (ERT) Method, because this method has good lateral and vertical resolution based on rock resistivity data. The trigger factors for land movement in Anjung Village, Pasanggrahan Baru, South Sumedang, among others: an increase in water content on the slopes and the slip plane. Increased water content is influenced by infiltration of rainwater as one of the triggers of land movement, can be detected by the Self Potential method (SP), while the slip plane can be detected by the method of Electrical Resistivity Tomography (ERT). Based on the results of the ERT and SP measurements, the results are: debris flow as a landslide plane (resistivity values: 31 – 170 Ohm.m and SP values: 5 – 13 mV), water table/water saturated layer (resistivity values: 1 – 13 Ohm.m and SP values: 14 – 34 mV), and breccias (resistivity values: 400 - 900 Ohm.m and SP values: 1-3 mV).Slip plane are estimated to be at boundary between the breccia and the material on it.Keywords: Land movement, resistivity, self potential, South Sumedang